Effect of solar eclipse on certain blood biochemicals in goats under intensive and extensive housing systems - Bharti, Vijay K; Singh, S P; Kumar, P; Mishra, R P; Bhavna, N (The Indian Journal of Animal Sciences, 2012)
During solar eclipse, unusual disturbances in the circadian rhythm affects the metabolism of animals through change in their biological clock. Therefore, the present study was designed to know the effects of solar eclipse on certain serum biochemicals of goats under intensive and extensive housing systems. Experiment was started from 19 July 2009 (control) to study the effects of solar eclipse (22July 2009). Adult goats (24) of both sexes were divided into 4 groups of male and female, viz. group1 (male extensive), group 2 (female extensive), group 3 (male intensive), and group 4 (female intensive). They were provided ration and water ad lib. during entire period of investigation. All the experimental goats were housed in extensive (groups 1 and 2) and intensive (groups 3 and 4) housing system to know the protective effect of different housing during solar eclipse. Daily (19–23 July 2009), we collected blood samples for analysis of serum T3, T4, thyroid stimulating hormone (TSH), alkaline phosphatase (ALP), alanine aminotransferase (ALT), Ca, and P. After solar eclipse (23 July 2009), TSH level was significantly increased in group 3. Serum ALT activity was significantly low in group1 on day of solar eclipse and end of experiment, whereas low activity of ALT was recorded in group 3 and4 at the end of experiment. Interestingly, high level of Ca in group 3 as well as ALP in group1 and 3 was recorded on solar eclipse day and was persistent till the end of experiment. However, serum T3 was significantly decreased in group 3 on solar eclipse day at the end of experiment. These findings are interesting and noticable in contest of observation on certain serum biochemical profile of goats during solar eclipse under different housing systems, which require further exploration.